Historical development of domestic army hand-to-hand combat as a sport - Irkhin, V.N.; Oldenburger, R.F.; Koreneva, M.S.; Repina, N.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify development trends in Russia of the military-applied sport "Army hand-to-hand combat". Methods and structure of the study. The following were used in the work: analysis and generalization of scientific literature, statistical data, practice of organizing army hand-to-hand combat (АHHС); studying the best practices of the training process; observation; conversation; generalization; study of documentation; specific methods of the history of pedagogy: historiographic, determinant-genetic and problem-genetic analyzes of the problem. Results and conclusions. The analysis of theoretical and empirical sources made it possible to identify the following features of the development of the АHHС as a military-applied sport in Russia from 1979 to the present: improvement of the organizational foundations and regulatory framework of the АHHС; geographical expansion of the АHHС in the regions of Russia; familiarizing pre-conscription and civilian youth with military hand-to-hand combat; improving tactics, increasing the speed and dynamics of the battle, increasing the entertainment of fights; increase in the number of competitions, athletes involved in АHHС (before 2010, positive dynamics, and after 2010 - negative); increased competition of АHHС from other types of martial arts; the outflow of children of school age 7-13 years old engaged in АHHС in the second or third years of training, improving the equipment of athletes.